Global Warming of 1.5°C IPCC Special Report on Impacts of Global Warming of 1.5°C above Pre-industrial Levels in Context of Strengthening Response to Climate Change, Sustainable Development, and Efforts to Eradicate Poverty (Physical Sciences, 2022)
This IPCC Special Report is a comprehensive assessment of our understanding of global warming of 1.5°C. It serves policymakers, decision makers, stakeholders, and all interested parties with unbiased, up-to-date, policy-relevant information. Also available as Open Access on Cambridge Core.